Autonomous Control of Voltage and Frequency in Parallel Inverters of Microgrid - Mrutunjaya Panda; Devara Vijaya Bhaskar; Surender Reddy Salkuti (e-Prime: Advances in Electrical Engineering, Electronics and Energy)
Integration of Distribution Generations (DGs) provides flexibility in power transmission. DGs reduce expenditure, expansion of transmission lines and transmission loss. DGs can work separately from the main grid with local loads and form a microgrid. In grid-connected mode, the voltage and frequency of the microgrid are regulated by the main grid. Voltage and frequency regulation in the islanding microgrid are crucial. This paper presents voltage and frequency control techniques for parallel inverters in microgrid. The proposed model works on close loop control of inverters and it can be used for plug-and-play operation of microgrid. The Microgrid model is developed in MATLAB/Simulink and the performance of the system is analyzed in grid-connected mode and isolation mode.